Clays and Clay Minerals, Vol. 55, No. 1, 18–35, 2007. - Ece, O¨. IsI˙K; Schroeder, Paul A. (The Clay Minerals Society, 2007)
Abstract—A field-mapping and crystal-chemical study of two alunite- and halloysite-rich deposits in the Turplu area, situated northwest of Balıkesir on the Biga Peninsula of northwest Turkey reveals a mineralogically diverse and a potentially economic clay deposit. The mineral assemblage along fault zones is dominated by halloysite and sometimes alunite. The alunite is nearly end-member in composition (a = 6.995 A ˚ , c = 17.195 A ˚ ) often occurring with a minor Ca phosphate phase. Of the two deposits studied, the more northerly mine contains more alunite relative to halloysite. Geochemical alteration indices suggest that the northern mine has experienced a slightly greater degree of hydrothermal modification. Halloysite is found in both hydrated and dehydrated states and assumes a tubular morphology. Observations by transmission and scanning electron microscopy are consistent with a model of halloysite dehydration, where the shapes transform from an open-hole tubular morphology to a closed-hole unfurled morphology. Mineral paragenesis includes the effects of initial deposition of volcanic tuffs and andesite on top of karstic terrain. The contact between altered volcanics and underlying limestones is irregular and appears to have provided a mechanism to flush both hydrothermal and meteoric waters through the volcanics. Periods of hydrothermal alteration (hypogene) contemporaneous with extensional and strike-slip faulting have resulted in alunite and halloysite deposits. Hydrothermal alteration is concentrated near the fault zones. Because of subsequent weathering (supergene) away from the fault zones, much of the andesitic volcanic rocks have been altered to a more smectite-rich and kaolinite-bearing assemblage. The deposits continue to be both plastically deformed in the alunite/halloysite regions and to undergo brittle deformation in the saprolitized volcanics. Tectonic deformation has mixed the contacts, such that limestone blocks are entrained into parts of the alteration zones. Gibbsite and gypsum are common weathering products associated with limestone block inclusions. Genetic models for the origins of alunite-halloysite deposits in NW Turkey should consider as possible influencing factors the underlying lithologies, the extent of hydrothermal alteration, and recent weathering by meteoric fluids. In the case of the Turplu deposits, karstic limestones, hydrothermal circulation of sulfate-rich waters, and a post-alteration history of meteoric weathering were all important factors in their formation.
Clay Mineralogy And Chemistry Of Halloysite And Alunite deposits In The Turplu Area, Balikesir, Turkey
Clays and Clay Minerals, Vol. 55, No. 1, 18–35, 2007. Clay Mineralogy And Chemistry Of Halloysite And Alunite deposits In The Turplu Area, Balikesir, Turkey. O¨. IsI˙K Ece; Paul A. Schroeder. DOI: 10.1346/CCMN.2007.0550102. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology; Acid-sulfate Thermal Waters; Alunite Deposits; Biga Peninsula; CryoSEM; Geochemistry; Halloysite Deposits; HRTEM; Hydrothermal Alteration; Hypogene vs. Supergene; SEM